2009
DOI: 10.1007/s11814-009-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bed height on the carbon dioxide capture by carbonation/regeneration cyclic operations using dry potassium-based sorbents

Abstract: The effect of bed height on CO 2 capture was investigated by carbonation/regeneration cyclic operations using a bubbling fluidized bed reactor. We used a potassium-based solid sorbent, SorbKX35T5 which was manufactured by the Korea Electric Power Research Institute. The sorbent consists of 35% K 2 CO 3 for absorption and 65% supporters for mechanical strength. We used a fluidized bed reactor with an inner diameter of 0.05 m and a height of 0.8 m which was made of quartz and placed inside of a furnace. The oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…However, the carbonation reaction rate of Na2CO3 was rather slow [16]. The attrition resistance (AI) and the corrected attrition index (CAI) of K2CO3 were higher than those of Na2CO3 sorbent [5,9,17]. For solid sorbent regeneration, the alkali metal required low regeneration temperature comparing with the alkali earth metal.…”
Section: Solid Sorbentmentioning
confidence: 99%
“…However, the carbonation reaction rate of Na2CO3 was rather slow [16]. The attrition resistance (AI) and the corrected attrition index (CAI) of K2CO3 were higher than those of Na2CO3 sorbent [5,9,17]. For solid sorbent regeneration, the alkali metal required low regeneration temperature comparing with the alkali earth metal.…”
Section: Solid Sorbentmentioning
confidence: 99%
“…KIER has developed a dry CO2 capture process using solid sorbents [37][38][39][40][41][42][43][44], and the research results on CO2 capture have been steadily reported in a laboratory-scale, a bench-scale, a pilot-scale process [1,2,[4][5][6]45,46]. Recently, Kim et al evaluated the CO2 capture performance of silica-PEI adsorbent in a lab.-scale TBS (twin bubbling fluidized-bed system) where 24 h preliminary tests were performed using 5 kg of adsorbent where the PEI with a molecular mass of 800.…”
Section: Introductionmentioning
confidence: 99%
“…KIER has developed dry CO 2 capture technology using solid sorbents, and related research is being conducted. The research results on CO 2 capture in a laboratory-scale device have been steadily reported, and a pilot-scale CO 2 capture process using dry adsorbents has been developed, consisting of a fluidized-bed-type adsorption reactor and a regeneration reactor (Yi et al, 2007(Yi et al, , 2008Yi, 2009Yi, , 2010Park et al, 2009aPark et al, ,b, 2011Kim et al, 2010Kim et al, , 2011. At present, the authors are continuing their research using dry adsorbents, and are developing more economical and energy-efficient dry adsorbents and the CO 2 capture process for commercial scale of 10 MWe (Park et al, 2013(Park et al, , 2014a(Park et al, ,b, 2016Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%